Activation of P2X7R- NLRP3 pathway in Retinal microglia contribute to Retinal Ganglion Cells death in chronic ocular hypertension (COH). (November 2019) - Zhang, Yujian; Xu, Yang; Sun, Qing; Xue, Shengding; Guan, Huaijin; Ji, Min
Abstract: Activation of P2X7 R is linked to the occurrence and development of glaucoma. The present study concentrated on the activated P2X7 R-NLRP3 pathway underlying the retinal microglia in retinal ganglion cells (RGCs) in chronic ocular hypertension (COH). Mouse COH model was set up to investigate the changes of P2X7 R-NLRP3 inflammatory pathway in vivo . Primary microglia cells and primary RGCs were cultured and purified in vitro experiments. The expression of P2X7 R, NLRP3, CASP-1, and ASC was detected and analyzed using Western blot, Quantitative polymerase chain reaction (qPCR) and immunofluorescence. Hoechst stains labeled nucleus to count microglia cells after experimental treatment. RGCs survival rate was examined utilizing LIVE/DEAD viability kit. The level of cytokines was measured by qPCR and enzyme-linked immunosorbent assay (ELISA). Consequently, the expression of P2X7 R, NLRP3, CASP-1, and ASC was raised in COH mice retina. The number of microglia cells was increased after addition of BzATP, the agonist of P2X7 R, to the culture medium of primary rat microglia cells. However, survival rates of RGCs decreased after addition of conditioned media to the RGC cultures. A438079 (100 μM), the inhibitor of P2X7 R, and Mcc950 (1 μM), the inhibitor of NLRP3, blocked the effect of P2X7 R activation in rat retinal microglia cells. Both inhibitors attenuated RGC death with the treatment of retina microglia cell conditioned medium (MCM). The production of some pro-inflammatory cytokines, such as TNF-α, CXCL-1, CSF-1, IL-6, IL-1β, and IL-18 was increased markedly with the activation of P2X7 R in microglia. However, the effect suffered as a result of A438079 and partially inhibited by Mcc950. These data suggested a role of P2X7 R -NLRP3 pathway in activated retinal microglia cell-mediated RGC damages in COH. Highlights: P2X7 R-NLRP3 pathway is activated during chronic ocular hypertension (COH) process. P2X7 R-NLRP3 pathway activation triggers retinal microglia cells proliferation. Retinal microglia cells mediates cytokine production through P2X7 R-NLRP3 pathway.